The Association of Placental Grading with Perinatal Outcomes: A Systematic Review and Meta-Analysis - Antonios Siargkas; Christina Pachi; Meletios P. Nigdelis; Sofoklis Stavros; Ekaterini Domali; Apostolos Mamopoulos; Ioannis Tsakiridis; Themistoklis Dagklis (Diagnostics)
Objective: Premature placental calcification (PPC) has been implicated in adverse perinatal outcomes, yet its clinical significance remains controversial. This meta-analysis aimed to quantitatively synthesize current data on the association between PPC, defined as grade 3 placental calcification before 36+6 weeks of gestation and adverse perinatal outcomes. Data Sources: A systematic search was conducted in MEDLINE, Scopus and The Cochrane Library from inception until 11 March 2025, to identify eligible studies. Study Eligibility Criteria: Observational studies including singleton pregnancies with PPC diagnosed via ultrasonography between 28+0 and 36+6 weeks of gestation and comparing them with pregnancies with Grannum grade 0, 1, or 2 placentas were considered eligible. Methods: Study quality was assessed using the Newcastle−Ottawa Scale, and the risk of bias was evaluated with the Quality In Prognosis Studies tool. The primary outcomes were small-for-gestational-age (SGA) neonates and preeclampsia. Heterogeneity was assessed using Cochran’s Q test and the I2 statistic. Meta-analyses were conducted using a random-effects model, with outcomes reported as relative risk (RR) or mean difference (MD) with 95% confidence intervals (CIs). Results: In total, nine cohort studies were included. PPC was associated with an increased risk of SGA (RR, 1.99; 95% CI, 1.46−2.70), preeclampsia (RR, 5.27; 95% CI, 2.24−12.40), fetal growth restriction (RR, 2.31; 95% CI, 1.30−4.09), preterm delivery (RR, 2.11; 95% CI, 1.00−4.45), suspected fetal hypoxia (RR, 1.71; 95% CI, 1.13–2.56), low 5 min Apgar score (RR, 2.28; 95% CI, 1.50−3.44) and neonatal intensive care unit admission (RR, 1.80; 95% CI, 1.02−3.18). No significant associations were found with fetal or neonatal death (RR, 2.75; 95% CI, 0.87−8.71), cesarean delivery (RR, 1.26; 95% CI, 0.90−1.78), gestational diabetes mellitus (RR, 1.17; 95% CI, 0.81−1.70), neonatal resuscitation (RR, 1.04; 95% CI, 0.92−1.16), birthweight (MD, −187.46 g; 95% CI, −413.14 to +38.21), or gestational age at birth (MD, −0.62 weeks; 95% CI, −1.36 to +0.11). A sensitivity analysis excluding high-risk-of-bias studies yielded consistent results. Conclusions: PPC is associated with several adverse perinatal outcomes, including SGA and preeclampsia. While the clinical significance of placental grading has remained limited in recent years, this study has shown that PPC may serve as an early indicator of placental insufficiency, warranting enhanced fetal surveillance and risk assessment in affected pregnancies. Further research is needed to refine its prognostic utility and integration into obstetric practice.